2018
DOI: 10.1108/pr-10-2016-0281
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial safety climate as resource passageways to alleviate work-family conflict

Abstract: Purpose The purpose of this paper is to examine a multidimensional mediating model of psychosocial safety climate (PSC) and work-family interference. More precisely, it tests the direct and indirect effects of PSC on work-family conflict (WFC)/family-work conflict (FWC)-time and WFC/FWC-strain via family-supportive supervisor behavior (FSSB). Design/methodology/approach The structural equation method was used to test the direct effect of PSC on WFC/FWC time and strain. As for the mediation effects, they were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 71 publications
1
24
0
5
Order By: Relevance
“…Mansour and Trembly 40 showed that PSC is related directly and negatively to conflict between the work and family. Dormann et al 41 indicated that lower levels of PSC among workers and employees increase psychosocial risk for the development of depression.…”
Section: Discussionmentioning
confidence: 99%
“…Mansour and Trembly 40 showed that PSC is related directly and negatively to conflict between the work and family. Dormann et al 41 indicated that lower levels of PSC among workers and employees increase psychosocial risk for the development of depression.…”
Section: Discussionmentioning
confidence: 99%
“…Les conséquences de ces conflits, notamment en lien avec l'insatisfaction dans la vie conjugale et familiale et les loisirs, ainsi qu'en lien avec l'épuisement, l'anxiété, la dépression, le stress et les troubles du sommeil, sont bien documentées (Davis et al, 2017;Kossek et al, 2011;Mansour et Mohanna, 2018). Sur le plan organisationnel, les répercussions concernent surtout la dégradation du climat de travail, la diminution du rendement, de la motivation et de l'implication et une augmentation des accidents du travail, des maladies professionnelles et des invalidités au travail (Bergs et al, 2018;Duxbury et Higgins, 2012;Mansour et Tremblay, 2018;McCutcheon et Morrison, 2017). Le conflit travail-vie personnelle peut nuire également à la qualité des services, particulièrement dans le secteur hôtelier où elle est un avantage concurrentiel (Mansour et Mohanna, 2018).…”
Section: Le Conflit Travail-vie Personnelleunclassified
“…Maintes études ont démontré les conséquences néfastes du conflit travail-vie personnelle sur les individus (Davis et al, 2017; Institut de la statistique du Québec, 2016;Mihelic et Tekavcic, 2014;Molino et al, 2013), sur les familles (Hoffman, et al, 2017; Institut de la statistique du Québec, 2016), sur les milieux de travail (Mansour et Tremblay, 2018;Schieman et al, 2018) ainsi que sur le système de santé (Baur et al, 2018;Bergs et al, 2018). Ces constats préoccupants incitent les acteurs du monde du travail (personnes en emploi, employeurs, syndicats) à chercher des solutions au conflit travail-vie personnelle.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…In my organization, the prevention of stress involves all levels of the organization a a Items included in the short PSC-4 scale (with permission, Hall et al 2010) 2012), confusion remains among the researchers. This can be seen from a constant need to explain and compare how PSC is distinct and even precedes some of the psychological safety-related concepts for nearly a decade (Mansour and Tremblay 2018;Huyghebaert et al 2018a). Although these constructs, safety climate, organizational support, and team psychological safety are very similar to PSC, even sharing some characteristics, they are theoretically and empirically distinct from each other.…”
Section: Psc Versus Other Related Constructsmentioning
confidence: 99%